Heterogeneous impacts of climate change on streamflow in typical watersheds of three mountain systems in Xinjiang, Northwest China - Chanjuan Zan; Yue Huang; Xiaohui Pan; Ping Chen; Weian Si; Jiabin Peng; Wenze Chen; Tie Liu (International Journal of Applied Earth Observations and Geoinformation)
Managing water resources in alpine, cold regions is increasingly complicated by climate change, which alters streamflow patterns and poses significant challenges to resource sustainability. This study addresses the critical issue of understanding how distinct hydrological watersheds respond to these climatic shifts. By examining four watersheds (BRW, the Burqin River Watershed; MRW, the Manas River Watershed; URW, the Urumqi River Watershed, and HRW, the Hotan River Watershed) with varying streamflow recharged characteristics, long-term streamflow was constructed by the SWAT model and Coupled Model Intercomparison Project Phase 6 (CMIP6) to evaluate the key climatic drivers of streamflow characteristics. Over the past 60 years, streamflow in typical watersheds has generally increased, with more frequent alternation between wet and dry periods. Notably, abrupt changes predominantly occurred in the 1990s, and these changes have shown a progressive delay as one moves geographically from north to south. Cold-season precipitation provides crucial solid water resources for alpine watersheds, with glacier melt driven by minimum and summer temperatures, while precipitation dominates other recharge systems. Future scenarios predict a significant increase in URW streamflow (approximately 18.3 %-25.8 %), while other watersheds are expected to see more moderate increases (around 4.6 %-12.9 %). Anticipated seasonal shifts include an earlier onset of streamflow advancing from April to March in the BRW, and delayed streamflow shifting to June in the HRW. Under the SSP5-8.5 scenario, the BRW shows a decrease in late summer and early autumn streamflow, while the URW may become increasingly dependent on rainfall, indicating a potential temperature threshold for streamflow changes. The earlier onset of spring snowmelt, combined with increased streamflow and reduced summer precipitation, heightens the risk of spring floods and summer droughts. Building emergency storage and adopting dynamic seasonal water allocation can reduce the impacts of streamflow changes and boost climate resilience.